PENINGKATAN HASIL BELAJAR SISWA DENGAN PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION BERBASIS LINGKUNGAN SEKOLAH - Ni Wayan Ekayanti; Gusti Ayu Dewi Setiawati (Jurnal Santiaji Pendidikan (JSP), 2017)
The purpose of this study is to analyze the improvement of student learning outcomes by using the school environment as a medium of learning with group investigation model. The method used in this research is quasi experiment using One Group Pretest-Posttest Design. The sample of this research is students of class VIIB SMPN 5 Denpasar. The results showed that there were significant differences in learning outcomes (p = 0,000 *) between before and after school-based learning by using group investigation model. So it can be concluded that the model of study group investigation based on school environment as a medium of learning can improve student learning outcomes.